Analysis of the Readiness of Culinary MSME Actors in Facing Mandatory Halal Certification 2026: A Phenomenological Study on the Minulyo Pacitan Market Traders Association - Citra Suci Setyani; Malta Anantyasari (Majapahit Journal of Islamic Finance and Management, 2026)
The Government of Indonesia set 17 October 2026 as the deadline for mandatory halal certification for food and beverage products produced by micro and small enterprises, as regulated in Law Number 33 of 2014 on Halal Product Assurance and Government Regulation Number 42 of 2024 on the Implementation of Halal Product Assurance. This policy presents challenges for micro and small culinary enterprises, including members of the Minulyo Market Traders Association in Pacitan Regency. This study aimed to explore the level of understanding, experiences, and readiness of business actors in facing the mandatory halal certification policy. The research used a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observation, and documentation involving government officers, association managers, and culinary business actors. Data analysis followed horizonalization, thematic clustering, and synthesis of essential meanings. The findings show that most business actors have awareness of halal certification requirements, but their understanding remains largely normative and does not yet extend to technical procedures such as application processes, document requirements, and assistance mechanisms. Furthermore, concerns about certification costs persist despite the availability of a free halal certification program provided by the government. The readiness level indicates that approximately eighty percent of business actors are cognitively ready, while twenty percent are not yet ready and require further assistance. This study concludes that the readiness of micro and small culinary enterprises is at the stage of cognitive readiness without operational readiness, indicating the need for more intensive community-based assistance strategies prior to the enforcement deadline.